The Visual Imagery Describing the Terrible Condition of the Victims of the War in Wilfred Owenâ€™s â€œDulce Et Docurom Estâ€ - Arielia Yustisiana (Humaniora Scientia, 2014)
The article is aimed to find out and analyze the visual imagery that describes the terrible condition of the victims of the war in Wilfred Owenâ€™s â€œDulce Et Docurom Estâ€. Wilfred Owen is the English War Poet. The article is written in order that the readers know about the gruesome condition of the war. The primary data of the article is a poem written by the war poet, namely, Wilfred Owen. There are some theories used to analyze the data. The basic theories are imagery and setting. There are seven imageries: visual imagery, auditory imagery, olfactory imagery, gustatory imagery, tactile imagery, kinaesthetic imagery and organic imagery. The poem is analyzed by using one poetic device, that is, visual imagery. Another theory is setting. In regard with the topic, the theory of setting is important because the analysis deals with the terrible condition of World War I. Library research is used to collect the data. Every line of the poem visualizes a very terrible depiction of discomfort and lack of dignity that has been experienced by the soldiers. The most vivid image of the victimâ€™s condition is when one of the soldiers feels shocked because of sudden gas attack. The particularly graphic nature of the speakerâ€™s descriptions emphasizes the idea of death in war. Keywords: visual imagery, setting, victim, World War I